Evidence brief: Preventing and managing infectious diseases among people who inject drugs in Ontario - Wilson, MG; Waddell, K; Lavis, JN (My University, 2019)
An assessment of what is known about problems related to infectious diseases among people who inject drugs, elements of a comprehensive approach for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of preventing and managing infectious diseases among people who inject drugs in Ontario
Keywords: infectious diseases; inject; Ontario; drugs